The Redistributive Effects of Fiscal Policy in Mali and Niger - Hounsa, Thierry; Coulibaly, Mohamed; Sanoh, Aly (World Bank, Washington, DC, 2019)
This study assesses the redistributive effects of fiscal policy in Mali and Niger. Fiscal policy is poverty increasing in Mali (by 2.4 percentage points) and Niger (2.5 percentage points). This is a result of primarily two factors: indirect taxes (value-added taxes and import duties) and direct fiscal transfers. Although the richest people in Mali and Niger pay the majority of indirect taxes, the poorest people pay a nonnegligible amount (more than 8 and 10 percent for the bottom three deciles, respectively). Although existing direct fiscal transfers have poverty-reducing effects, they are too small (Mali) or not well targeted (Niger).